An Analysis of Student’s Skills in Writing Descriptive Text for Tenth Grade in SMA Negeri 1 Banjar - Kadek Tommy Praditha; Putu Eka Dambayana; Luh Gd. Rahayu Budiarta (Jurnal Penelitian Mahasiswa Indonesia, 2022)
The present study aims to describe Students’ Skills and the difficulty faced by students in Writing Descriptive Text for Tenth Grade Students in SMA Negeri 1 Banjar. The design applied was qualitative research. The research subjects are X MIPA 1 Students of SMAN 1 Banjar who had difficulties when writing descriptive text. The data of this research are the result of students’ test results and the students’ answers in the open-ended questionnaire. The research instruments were a test and an open-ended questionnaire. Data reduction, data display and drawing conclusions were used to analyse the data. The result of this research shows that the students of X MIPA 1 writing skills are relatively low with a score of 60 which is lower than the target score of ≤ 70 and the students of X MIPA 1 have difficulty in writing descriptive text, the difficulties are difficulties in content, difficulties in grammar, and difficulties in vocabulary, difficulties in organization and spelling.